Ellipse in den deutschen und polnischen Dialogen - Prokop, Izabela (Wydawnictwo Naukowe UAM, 1984)
The article includes in first part the review of some definitions of elliptic constructions, in particular a presentation of views of Soviet linguists. In part two the author describes and classifies elliptic utterances. The corpus are 32 dialogues taken from belles-lettres.